ADRIANA MARGARETA DANCUS: Exposing Vulnerability: Self-Mediation in Scandinavian Films by Women. Intellect, Bristol 2019. Pp. 148. ISBN: 978-1-78320-988-0. Issue 1 (2020) - VIITANEN, ESSI
No abstract available